Tribute, hope and reconciliation - Moltmann, Jürgen (HTS teologiese studies, 2017)
This article represents a trilogy of tribute to and by Jürgen Moltmann on 05 and 06 April 2017 during the centenary celebrations of the Faculty of Theology at the University of Pretoria and the conferment of an honorary doctorate to Moltmann. The first tribute to Prof. Moltmann is an address from the General Secretary, World Council of Churches, Geneva, Switzerland, Rev. Dr Olav Fykse Tveit. In this he honours Professor Moltmann’s prophetic reflection on how theology can bring the living God we all believe in to the world today, so that human beings and the entire creation can experience the fullness of life that God promised to us all. The second tribute is authored by Klaus Nürnberger, in which he reflects on Moltmann’s legacy for South Africans. The second part is Prof. Moltmann’s acceptance speech at the graduation ceremony on 06 April when he addressed the new graduandi and their families and friends at the Rembrandt Hall, University of Pretoria. He inspires the newly graduandi by saying: ‘In the end – there is a beginning. Young men and women, let your hope arise. We have so much of sick and dying hope around us. There is resignation. There is the arrogance of the powerful, and there is the apathy of powerless. Drop arrogance and learn to listen to others. Get out of apathy and lift up your head and raise your voices. Break out of indifference and get involved. Life is so beautiful’. The last section echoes Moltmann’s lifelong emphasis on the living power of hope and focuses on the power of forgiveness to mend broken relationships. This is not an easy task, and where it is up to humanity, utterly impossible to cross the divides the human condition can create. Moltmann focuses on how the reconciliation of Christ with humanity creates bridges for humanity to reconcile with one another. Reconciliation restores relationships and opens a ‘gateway’ to the future. In this way, Moltmann highlighted the theme of the centenary celebration of the Faculty of Theology of the University of Pretoria.